Presence and implication of Candida spp. in patients with peri‐implantitis enrolled in a supportive peri‐implant therapy program of the Basque Country ( Spain ). A case–control study - Lafuente‐Ibáñez‐de‐Mendoza, Irene; Marichalar‐Mendia, Xabier; García‐De‐La‐Fuente, Ana María; Quindós‐Andrés, Guillermo; Eraso‐Barrio, Elena; Martínez‐Conde‐Llamosas, Rafael; Fernández‐Jiménez, Aitziber; Aguirre‐Urizar, José Manuel (Clinical implant dentistry and related research, 2023)
The peri-implant sulcus is a good niche for infectious colonization such as Candida spp. In this study, the level of Candida spp. fungal colonization is analyzed in patients with peri-implantitis under supportive peri-implant therapy, as well as its correlation with the main clinicopathological data. A case-control study was carried out on 161 patients treated with dental implants, 80 with PI and 81 without PI, which corresponded to 91 women and 70 men, whose mean age was 60.90 years. A specific protocol was completed for the clinical and implant data. Microbiological samples were taken by oral rinse and with paper tips from the peri-implant sulcus. For the quantitative and qualitative analysis Candida Chromogenic Agar/CONDA plates were incubated for 72 h at 36 + 1°C. Fungal growth was considered active when having more than 50 CFU. Specific Candida spp. cultures were later confirmed by API ID 32C and PCR. Fungal growth was achieved in 28% of oral rinse and 6.75% of peri-implant fluid samples. No significant differences were recognized between study groups. Most of the cultures (>65%) showed more than 50 CFU. The most frequent species were Candida albicans and Candida parapsilosis. There was no association between different PI risk factors and fungal data. The presence of Candida spp. in the oral cavity of patients with dental implants was related to total edentulism and the use of implant-fixed complete prosthesis implant-retained removable prosthesis. These results suggest that there is no link between PI and presence of Candida in patients with dental implants undergoing regular supportive periodontal therapy.